A dual role for pleiotrophin in modulating inflammation and myelination in the presence of chondroitin sulfate proteoglycans after nervous system injury - Gupta, Somnath J.; Churchward, Matthew A.; Todd, Kathryn G.; Winship, Ian R. (Frontiers in Cellular Neuroscience, 2025)
Chondroitin sulfate proteoglycans (CSPGs), key components of the extracellular matrix and the glial scar that forms around central nervous system (CNS) injuries, are recognized for hindering neuronal regeneration. We previously demonstrated the potential of pleiotrophin (PTN) to induce neurite outgrowth even in the presence of inhibitory CSPGs. The effects of PTN on microglia and oligodendrocytes are not well described. Here, we examined how PTN administration alters the differentiation of oligodendrocyte precursor cells (OPCs) into mature oligodendrocytes in the presence of CSPGs using in vitro cell culture model. Moreover, we explored the effects of PTN on the inflammatory activity of microglia with and without inflammatory stimulation (IFN-γ) in a CSPG-rich environment. The data showed that the CSPG matrix inhibited the differentiation of OPCs into mature oligodendrocytes. PTN induced dose-dependent differentiation of OPCs into mature oligodendrocytes, with an optimal effect at 10 nM PTN. Moreover, PTN modified the immunological response of microglia in the presence of CSPGs, with reduced proinflammatory activity that was further reduced by PTN administration, in contrast to the increased release of matrix metalloproteinases (MMP 9). However, when IFN-γ-activated microglia were treated with PTN, proinflammatory signaling was stimulated at higher PTN concentrations (10 nM and 100 nM). Overall, our results indicate that PTN can overcome the inhibitory effect of CSPGs on the differentiation of OPCs into oligodendrocytes and can modulate inflammation mediated by CSPGs from microglia. Collectively, these findings demonstrate that PTN can effectively counteract the inhibitory effects of CSPGs on the differentiation of OPCs into mature oligodendrocytes while also modulating microglial responses to reduce proinflammatory activity and increase MMP-9 release. Thus, PTN has great potential to improve remyelination and neuroprotective strategies in the treatment of demyelinating diseases or any injury.